A Novel RLWE-Based Anonymous Mutual Authentication Protocol for Space Information Network. (25th August 2020) - Guo, Junyan; Du, Ye
Abstract : Currently, space information network (SIN) has become an increasingly important role in real life. As a large heterogeneous wireless network, SIN can better provide global mobile services to users anytime and anywhere, even in extreme geographic environments. In addition, there is no need to build the communication base-stations every few kilometers on the ground to ensure high service quality, which greatly reduces the construction costs and can be used as an economical communication method in sparsely populated areas. So there is a trend that more and more end users are more likely to get SIN services than traditional terrestrial cellular networks. However, due to the openness and publicity of the satellite wireless channel and the limited resources of the satellite nodes, the privacy and security cannot be perfectly guaranteed and may even be vulnerable to attacks initiated by the adversary such as replay attacks, impersonation attacks, and eavesdropping attacks. To improve the access security of SIN, researchers have proposed a series of authentication protocols based on different cryptographic assumptions. Nevertheless, existing research shows that these protocols cannot meet the requirements of higher and higher security and short authentication delay. In addition, these protocols are mainly based on public key cryptography mechanisms such as DLP and ECDLP, which can be solved by postquantum computers in polynomial time, so these protocols will no longer be secure. To solve the vulnerability of these protocols, in this paper, we propose a new RLWE-based anonymous mutual authentication and key agreement protocol, which guarantees higher security with low computational overhead even in the postquantum era. Detailed security analysis shows that our protocol meets security requirements and is resistant to a variety of known attacks. Besides, combining security comparison and performance analysis, our proposed protocol is more practical than other protocols in SIN.